A Review of Real-Time Database System and Distributed Database System: Exploring Approaches for Adapting Database Systems to Real-Time Distributed Data Processing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today’s Real-Time Systems (RTS) are defined by managing massive amounts of scattereddata making Real-Time distributed data processing a reality. Large company houses need to undertakedispersed processing for numerous reasons, and they frequently must do it in order to stay competitive.So, efficient database management methods and protocols for accessing and changing data areessential to fulfil temporal limitations of supported applications. Therefore, new research in DistributedReal-Time Database Systems (DRTDBS) is needed to study various approaches of adapting databasesystems technology to Real-Time systems. In this paper the Real-Time Database System and DistributedDatabase System are discussed.